2014
DOI: 10.1371/journal.pone.0116452
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Preoperative Nuclear Morphometry to Evaluating Risk for Cervical Lymph Node Metastasis in Oral Squamous Cell Carcinoma

Abstract: BackgroundWe previously reported the utility of preoperative nuclear morphometry for evaluating risk for cervical lymph node metastases in tongue squamous cell carcinoma. The risk for lymph node metastasis in oral squamous cell carcinoma, however, is known to differ depending on the anatomical site of the primary tumor, such as the tongue, gingiva, mouth floor, and buccal mucosa. In this study, we evaluated the applicability of this morphometric technique to evaluating the risk for cervical lymph node metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Neck node metastasis is an important prognostic factor in oral SCC. However, primary tumor site was not found to be associated with cervical lymph node metastasis under multivariable regression analysis on 88 patients only collected retrospectively from 1981 to 2012 [5]. Under another study (Kailiu Wu et al (2015)) histological grade and neurovascular invasion were associated with the risk of cervical lymph node metastasis of early tongue SCC (n = 171) [13].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Neck node metastasis is an important prognostic factor in oral SCC. However, primary tumor site was not found to be associated with cervical lymph node metastasis under multivariable regression analysis on 88 patients only collected retrospectively from 1981 to 2012 [5]. Under another study (Kailiu Wu et al (2015)) histological grade and neurovascular invasion were associated with the risk of cervical lymph node metastasis of early tongue SCC (n = 171) [13].…”
Section: Discussionmentioning
confidence: 91%
“…Metastasis to cervical lymph nodes may be because of filtering effect of the rich lymphatic system. Nodal metastasis strongly influences the five year survival rate, prognosis of oral cancer [5] and significantly affects regional control and survival [6] [7] [8] [9] [10]. Also, Metastasis in nodes is a complex multi-step process and cannot be explained by enlargementonly [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear polymorphisms have been associated with poor prognosis in head and neck cancer . Manual count of nuclei in this study identified >7 large and >6 atypical nuclei per image to detect dysplastic lesions.…”
Section: Discussionmentioning
confidence: 82%
“…Nuclear polymorphisms have been associated with poor prognosis in head and neck cancer. 21,22 Manual count of nuclei in this study identified >7 large and >6 atypical nuclei per image to detect dysplastic lesions. In analogy, it was shown that only ≥3 very large, anaplastic nuclei and ≥3 multinucleated cells are correlated to worse survival in p16+ oropharyngeal carcinoma.…”
Section: = 143 Images) = 94 Images) Automentioning
confidence: 86%
“…Our result was in accordance to studies conducted by various authors. 8,[20][21][22][23][24][25] The metastasis to lymph nodes manifests when specific cellular and nuclear changes occur in tumor cells, which represent a distinctive clone. The tumor cells undergo certain changes phenotypically that aids in transportation of these cells to the lymphatic stream.…”
Section: Discussionmentioning
confidence: 99%